FUNGSI DAN KATEGORI SINTAKSIS DALAM KALIMAT TEKS CERITA ANAK PADA BUKU NONTEKS KEMDIKBUD “TIDAK BISA TIDAK” - Ghina Qolbi; Sawardi, FX (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
Children's story text is a form of literary work that has strategic value in character building and developing children's literacy. Children's story texts hold linguistic richness that is interesting to study, especially in the aspect of syntax, which is the study of the structure and function of sentence building elements. This study aims to describe the syntactic structure by analyzing the use of functions and categories in sentences contained in children's story texts. The problem of this research is how syntactic functions and categories are represented in sentences in children's story texts. The data used are sentences that contain syntactic functions and categories. The data source comes from the text of a children's story titled “Tidak Bisa Tidak” in the Kemdikbud nontext book level B3. This research uses the listening method with note-taking technique in collecting the data. The analysis method used is agih method. The results obtained from this study show the existence of syntactic functions which include subject, predicate, object, description, and complement. In addition, there are categories found including nouns, verbs, adjectives, adverbs, noun phrases, verb phrases, and pronomines.